2012
DOI: 10.1007/s00705-011-1222-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of ribavirin and pleconaril antiviral activity against enterovirus 71 infection

Abstract: Enterovirus 71(EV71) causes recurring outbreaks of hand, foot and mouth disease and encephalitis leading to complications or death in young children. More effective antiviral drugs are needed to prevent or reduce EV71-related disease and complications. However, there are no standard models currently in use to evaluate activity against EV71 infection both in vitro and in vivo. In this study, the activity of ribavirin and pleconaril against EV71 infection was evaluated in two models. An in vitro EV71 infection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 38 publications
1
58
1
Order By: Relevance
“…Ribavirin is a nucleotide analogue that has antiviral activities against a variety of RNA (9,12) and DNA (9) viruses, including HEV71 (11). Ribavirin has been shown to diminish viral protein translation and RNA replication via three activities: as a mutagen by incorporation into nascent viral RNA molecules (8)(9)(10)12), by the inhibition of IMP dehydrogenase (IMPDH), which results in a decrease in intracellular GTP levels (25)(26)(27), and by immunomodulatory effects, including a switch in the T-helper cell phenotype from type 2 to type 1 (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribavirin is a nucleotide analogue that has antiviral activities against a variety of RNA (9,12) and DNA (9) viruses, including HEV71 (11). Ribavirin has been shown to diminish viral protein translation and RNA replication via three activities: as a mutagen by incorporation into nascent viral RNA molecules (8)(9)(10)12), by the inhibition of IMP dehydrogenase (IMPDH), which results in a decrease in intracellular GTP levels (25)(26)(27), and by immunomodulatory effects, including a switch in the T-helper cell phenotype from type 2 to type 1 (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity of ribavirin is thought to be due to its ability to increase the nucleotide incorporation error rate during both DNA and RNA viral replication (9)(10)(11).…”
mentioning
confidence: 99%
“…In one study, antiviral activity of pleconaril was reported in EV71-infected mice (20). Other studies, however, reported a lack of in vitro anti-EV71 activity of pleconaril (21)(22)(23).…”
mentioning
confidence: 99%
“…The EV71 BrCr strain was demonstrated to induce neurological manifestation of tremor, ataxia, and brain edema in cynomolgus monkeys [16]. Moreover, EV71 BrCr infected mice also developed limbs paralysis and encephalitis [17]. SCARB2 (also known as Lysosomal Integral Membrane Protein II, LIMP II, LGP85 or CD36b like-2) is composed of 478 amino acids and belongs to the CD36 family, which includes CD36 and scavenger receptor B, member 1 (SR-B I and its splicing variant SR-B II) [18,19].…”
Section: Introductionmentioning
confidence: 99%